1999
DOI: 10.1046/j.1439-0450.1999.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Septicaemic Colibacillosis in Japanese Quail (Coturnix coturnix japonica)

Abstract: We have carried out an aetiological and pathological study of an outbreak of septicaemia caused by the O165 serogroup of Escherichia coli in Japanese quail (Coturnix coturnix japonica) which resulted in high mortality (90%). After treatment with amoxicilin in drinking water (200 mg/l), morbility and mortality rates dropped markedly. Microbiological studies showed that the organism responsible was an atypical E. coli strain, on the basis of the non-fermentation of lactose (ONPG-), which belonged to the O165 ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…This is in agreement with the findings in other wild birds (Fiennes 1959;Hanssen 1979;Brittinham et al 1988;Glünder 1981Glünder , 2002. In contrast, E. coli is a common parasite of captive birds (Hanssen 1979;Naldo et al 1998;Arenas et al 1999), as found here in farmed partridges.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…This is in agreement with the findings in other wild birds (Fiennes 1959;Hanssen 1979;Brittinham et al 1988;Glünder 1981Glünder , 2002. In contrast, E. coli is a common parasite of captive birds (Hanssen 1979;Naldo et al 1998;Arenas et al 1999), as found here in farmed partridges.…”
Section: Discussionmentioning
confidence: 51%
“…Some gallinaceous birds have also been described as potential carriers of these bacteria, both in the intestine (Benskin et al 2009), and also in meat (Paulsen et al 2008;Arenas et al 1999). Some studies suggest marked differences between the microbiological conditions in the small intestine and caeca of wild and captive birds (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…manifestations (Barnes et al, 1997). Colisepticemia is one of the avian disease manifestations of E. coli infection and has been reported in chickens, turkeys and quails (Barnes et al, 1997;Arenas et al, 1999). In our case, E. coli was isolated from specimens of liver, spleen, and intestine.…”
Section: E Coli Infection In Avian Species Can Cause Many Clinicalmentioning
confidence: 46%
“…To date the presence of APEC has been related to extra-intestinal disease in chicken, turkeys (Meleagris gallopa) and Japanese quail (Coturnix coturnix japonica) (Allan et al, 1993;Arenas et al, 1999;Ramírez et al, 2009;Salehi & Ghanbarpour, 2010), but not as yet in red-legged partridges. The only existing information on the implication of E. coli in disease in red-legged partridges consists of a report describing an outbreak of naturally occurring attaching and effacing E. coli in farmed red-legged partridges (La Ragione et al, 2004).…”
Section: Discussionmentioning
confidence: 99%